2022
DOI: 10.1007/s00192-022-05126-4
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcome measures for pain in women with pelvic floor disorders: a systematic review

Abstract: Introduction and hypothesis Patient-reported outcome measures (PROMs) are helpful instruments when measuring and reporting changes in patient health status (Al Sayah et al. J Patient Rep Outcomes 5 (Suppl 2):99, 2021) such as the health-related quality of life (HrQoL) of women with pelvic organ prolapse (POP) and stress urinary incontinence (SUI). The Australasian Pelvic Floor Procedure Registry (APFPR) aims to increase capacity for women to report surgical outcomes through the collection of HrQo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Based on the findings of our systematic review [10] and themes arising from analysis of the interview transcripts, a conceptual framework for an ideal pain instrument for the APFPR was developed. The findings were summarised into a comprehensive diagram and domains from the analysed themes were synthesised, where elements of pain important to women following mesh surgery for POP and SUI and their clinicians were described [16].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Based on the findings of our systematic review [10] and themes arising from analysis of the interview transcripts, a conceptual framework for an ideal pain instrument for the APFPR was developed. The findings were summarised into a comprehensive diagram and domains from the analysed themes were synthesised, where elements of pain important to women following mesh surgery for POP and SUI and their clinicians were described [16].…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the need for the female voice to inform researchers on what is important. Our previous research has identified that the instruments included in pelvic floor registries are not particularly helpful for women following surgery for POP and SUI [9,10]. It remains a complex situation as pain may exist because of a woman's original PFD; typical post-operative pain; or pain following mesh surgery due to complications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations